Degradation of outdoor spaces in condominiums of M’sila City (Algeria): causes and effects - Djamel, Dahdouh; Brahim, Nouibat (Technium Social Sciences Journal, 2022)
The review of the scientific literature has shown that the external spaces of collective condominiums play an essential role in the inhabitant well-being and contribute positively to their moral health. However, in Algeria, these spaces suffer from many hazards, the negative effects of which are more and more palpable both on the urban and social levels. In the absence of development or lack of adaptation to the socio-cultural needs of their users, they appear to be abandoned, given the major misuse of uses promoting unhealthy conditions, insecurity and ill living. Like the Algerian cities, the external spaces of the condominiums of the city of M’sila are not immune to these urban diseases. By choosing three condominiums as a case study, this article attempts to assess the relationship that could exist between the quality of development and management (upkeep and maintenance) with the level of degradation of the exterior spaces of these condominiums, and this, through the survey technique. In a second step, and through the technique of semi-structured interview, the level of user satisfaction will also be assessed. Statistical data processing will be done using Sphinx plus² software (version5).